The Witness of the Armenian Genocide from Armtan - Avagyan, Artsrun (Bulletin of Yerevan University B: Philology, 2023)
The article highlights the Constantinople period of the life of Hakob Mndzuri (Hakob Temurchyan), the classic author of Armenian literature. As a result of the genocide, Hakob Mndzuri had to live his whole life away from his native Armtan, because the population of his native village Armtan, as well as his entire family, including his four children, were exiled and slaughtered. Mndzuri, the author of several short stories published in Constantinople based “Mehean” and “Ostan” journals, plunges into the literary-creative sphere, becoming one of the pioneers of nostalgic literature and Diaspora Armenian literature. His main theme was the village and the peasant, native nature and animal world, which, by generalizing, condensed the deep mystery of work and creation as a counterweight to slaughter and destruction. In almost all of his stories, he is present, sometimes as a participant in the unfolding events, sometimes as an eyewitness, sometimes as an interlocutor with the characters he created and the reader. His stories, apart from their artistic values, are also geography, ethnography, documentation of folk life, manners and customs, but above all, it is a documentation of the Armenian people, its testimony, a literature which, when reading, raises the question in the reader’s mind, who are those people and why are they gone? Although most of his stories consist of up to 2-3 pages, his four books, novels and writings published in the press in their entirety form a single novel, which can be called a legend of the village of Armtan in Western Armenia addressed to the present and future generations, for the perpetuation of the native land and of all the martyrs.